Перспективні напрями розвитку системи оцінки кадрів громадської безпеки - Фатхутдінов, Василь Гайнулович; Фатхутдинов, Василий Гайнулович; Fathutdinov, Vasilij (Одеса : Юрид. л-ра, 2014)
In the paper we have studied the certification as a tool for assessing public safety personnel. Set problem points in the existing system of public safety personnel evaluation. Identified areas of development assessment of public safety personnel. The necessity of the gradual introduction of a system of annual evaluation of employees. The main purpose of assessment should be to improve the impact assessment on the effectiveness of the activities of public safety personnel, and strengthening ties with the assessment of the further service. Necessity of research regulatory existing systems currently in the annual assessment of civil servants. The purpose of this analysis is to determine the prospects for its extension to public safety personnel, and – identification of common problems in its functioning with the aim of preventing them in the development and implementation procedures annual assessment of public safety personnel.
Фатхутдінов В. Г. Перспективні напрями розвитку системи оцінки кадрів громадської безпеки / В. Г. Фатхутдінов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 353-358.
Keywords: атестація; кадри; громадська безпека; щорічне оцінювання; аттестация; кадры; общественная безопасность; ежегодное оценивание; certification; human resources; public safety; annual evaluation